Study on the heat-recovering performance of solar-gas heating system - Hao, Hong; Yu, G.; Yao, J.; Feng, G.; Li, Y. (Editorial Department of Journal of Shenyang Jianzhu University, 2016)
This paper was proposed to investigate the heat-recovering performance of solar-gas heating system in a residential building in Shenyang to study the compatibility between the engine, cylinder cooler and waste heat saver. According to the components design on basic construction load of the solar-gas heat pump heating system, a set of model was established and the results showed that the cooling water flow rate increased by 0.285~1.21 g/s when the engine velocity accelerated every 100 r/min, therefore, increase the circulation heating water temperature by 2~5?, and the circulating water temperature increased to 47~50?; The optimal energy utilization was obtained when the waste heat recovery was 0.7 based on the rated power. To maintain a constant rated power, the resistance of the exhaust heat exchanger was controlled less than 190.27 kPa; With engine speed raised every 100 r·min-1, the waste heat recovery unit area added 0.173 m2. It can be concluded that recovering the waste heat of gas-engine in a proper way will guarantee the high efficiency of the engine, and improve the energy utilization.